Implementation of Stop Motion Graphic Animation Video as Learning Media to Improve Students' Ecoliteracy Ability on the Subject Matter of Environmental Change - Rahmatia Karuana; Masra Latjompoh; Abubakar Sidik Katili (Jurnal Penelitian Pendidikan IPA, 2023)
This study aimed to determine the increase in student’s ecoliteracy skills through the implementation of stop motion graphic animation video as the learning media on the subject matter of environmental change. In conducting the study, it used the Pre-experiment method in the form of a quasi-experiment, one group pretest-posttest. The results of this study showed that, there was a significant increase in students’ ecoliteracy skills obtained in pretest by students before implementing the stop motion graphic animation media as 71.2. Meanwhile, the implementationof it showed an increase as the result of the posttestobtained an increased average value of 90.1. The use of stop motion graphic animation was applicable to be used as one of the learning media in biology. This was because it fostered students’ interest in the learning process. Therefore, based on the results of this study, it can be concluded that the stop motion graphic animation video can be used to improve students’ ecoliteracy skills significantly